PROFILE OF COLO-RECTAL CANCER AT HASAN SADIKIN HOSPITAL BANDUNG - Mochamad Aleq Sander (University of Muhammadiyah Malang, 2012)
Colo-rectal cancer represent one of the most third malignancy in the world and second caused of death in US. In Indonesia amount of colo-rectal cancer was sequence to 10 (2.75%) after others cancer (cervix, breast, lymph, skin, nasofaring, ovarium, soft tissue, and thyroid). Key success in treatment of this cancer was that they found in early stage and followed curative therapy. Unfortunately in Indonesia they came after advanced stage and they had low survival. Colo-rectal cancer need multimodalities and in Indonesia not yet found uniformity in approach of therapy. The aim of research is to know the epidemiology, clinical symptom, diagnosis, therapy, prognosis. Descriptive study with retrospective design. Total sampling was all outpatient in digestive department of Hasan Sadikin Hospital of Bandung with colo-rectal cancer from January 2005 up to December 2008. 163 eligible respondens who had age below 40 yo 19 (11,7%) and above 55 yo 61 (37,4%). Female 89 (54,6%). Rectum was the most location that is 115 (70.6%). A lot of stadium was Dukes B2 that is 33 (20,2%). The most clinical manifestation was defecate blood that is 76 (46,6%). Adenocarcinoma well differentiated was the most common type of histology that is 93 (57,1%). Miles Procedure was 21 (12.9%) and hemicolectomy and colostomy were 19 (11,7%). The prognosis was healing 90 (55,2%), not yet healed 24 (14,7%), not control 38 (23,3%), and who control in the other place 2 (1,2%). Conclusion: mostly of colo-rectal cancer was found in fifth decade. A lot of cancer location was rectum and adenocarcinoma as a type of histology. Dukes B2 and defecate blood had most proportion, blood excision biopsy, and followed by radical mastectomy were the most therapy procedure. Miles procedure was the most common therapy in rectal cancer.